Mesoporous Prussian blue nanoparticle neuroconduit for the biological therapy targeting oxidative stress reduction, inflammation inhibition, and nerve regeneration - Junyi Zhu; Yijia Zhang; Yinuo Sun; Fangzheng Yu; Yang Lu; Qianqian Hu; Jiali Guo; Haijuan Zhang; Tianling Chen; Feifei Lian; Jian Wang; Xiaokun Li; et al. (Journal of Nanobiotechnology)
Abstract The applications of nanomaterials in regenerative medicine encompass a broad spectrum. The functional nanomaterials, such as Prussian blue and its derivative nanoparticles, exhibit potent anti-inflammatory and antioxidant properties. By combining it with the corresponding scaffold carrier, the fusion of nanomaterials and biotherapy can be achieved, thereby providing a potential avenue for clinical treatment. The present study demonstrates the fabrication of a Mesoporous Prussian blue nanoparticles (MPBN) functionalized Inverse Opal Film (IOF) neuroconduit for peripheral nerve repair through reverse replication and freeze-drying techniques. The binding of MPBN to the neuroconduit can effectively decreasing reactive oxygen species and inflammatory factors in the vicinity of the residual nerve, thereby providing protective effects on the damaged nerve. Furthermore, comprehensive behavioral, electrophysiological, and pathological analyses unequivocally substantiate the efficacy of MPBN in increasing nerve structure regeneration and ameliorating denervation-induced myopathy. Moreover, MPBN enhances the antioxidant capacity of Schwann cells by activating the AMPK/SIRT1/PGC-1 pathway. The findings suggest that MPBN, a biocompatible nanoparticle, can safeguard damaged nerves by optimizing the microenvironment surrounding nerve cells and augmenting the antioxidant capacity of nerve cells, thereby facilitating nerve regeneration and repair. This also establishes a theoretical foundation for exploring the integration and clinical translation between nanomaterials and biotherapy.